Mango (Mangifera indica L.) by-products and their valuable components: a review - Jahurul, Md. Haque Akanda; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Al-Juhaimi, Fahad Y.; Kar-Lin, Nyam; Norulaini, N.A.N.; Ferdosh, Sahena; Mohd Omar, Ab. Kadir (Elsevier, 2015)
The large amount of waste produced by the food industries causes serious environmental problems and also results in economic losses if not utilized effectively. Different research reports have revealed that food industry by-products can be good sources of potentially valuable bioactive compounds. As such, the mango juice industry uses only the edible portions of the mangoes, and a considerable amount of peels and seeds are discarded as industrial waste. These mango by-products come from the tropical or subtropical fruit processing industries. Mango by-products, especially seeds and peels, are considered to be cheap sources of valuable food and nutraceutical ingredients. The main uses of natural food ingredients derived from mango by-products are presented and discussed, and the mainstream sectors of application for these by-products, such as in the food, pharmaceutical, nutraceutical and cosmetic industries, are highlighted.